Lifestyle Characteristics of Students who are Overweight, Obese, or have Normal Body Weight - Matejek, Črtomir; Kukovica, David (Revija za elementarno izobraževanje, 2025)
This study examines the differences in body composition and lifestyle habits between normal-weight (NW) and overweight/obese (OW&O) university students. A sample of fifty-five students aged 21–25 years completed validated questionnaires (HLPCQ, IPAQ-SF, WHO-5) and underwent body composition analysis using the InBody 270 device. Statistical analyses included independent sample t-tests and Cohen’s d effect sizes. OW&O students had significantly higher scores for body fat, fat-free mass, and skeletal muscle mass. While body composition differences were evident, lifestyle habits did not significantly differ between weight groups. Bias in lifestyle and well-being self-assessment calls for the development of more objective assessment tools and further research.
Keywords: body composition, eating habits, sleeping habits, physical activity, social balance.